1985
DOI: 10.1002/app.1985.070301206
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and equilibrium swelling of DVB-crosslinked polystyrene particles

Abstract: synopsisThe dynamic and equilibrium swelling behavior of polystyrene microparticles crosslinked with divinyl benzene was investigated in methyl ethyl ketone and cyclohexane. The dynamic studies gave new information about the mechanism of penetrant transport in this polymer. The equilibrium studies were used to determine important parameters of the crowslin&d structure of these systems, including the average molecular weight between crosslinks, M ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…From this table, the "n" for both hydrogels decrease with the increase of AN content. Barr-Howell and Peppas [17] reported that the increase of swelling degree of PS in different solvent caused by the decrease in crosslinking density resulting in an increase in the molecular weight between crosslinks (M c ). When we compare same compositions for unamidoximated and amidoximated hydrogels, the swelling degree values are increased although M c is constant resulting in an increase in "n".…”
Section: Resultsmentioning
confidence: 98%
“…From this table, the "n" for both hydrogels decrease with the increase of AN content. Barr-Howell and Peppas [17] reported that the increase of swelling degree of PS in different solvent caused by the decrease in crosslinking density resulting in an increase in the molecular weight between crosslinks (M c ). When we compare same compositions for unamidoximated and amidoximated hydrogels, the swelling degree values are increased although M c is constant resulting in an increase in "n".…”
Section: Resultsmentioning
confidence: 98%
“…59 For determining this parameter, the end-to-end distance in the freely jointed state is determined as (9) where l= 1.54A and the number of links, N=JcMc/M 0 and Jc= 2. The end-to-end distance in the unperturbed state is calculated through the characteristic ratio C" = I 0 (10)…”
Section: Network Studiesmentioning
confidence: 99%
“…1967). This method-or its inverse, measurement of weight loss from material saturated with solvent-has been applied to measure swelling of many other materials in addition to paint, mostly polymer networks of various types (Barr-Howell and Peppas 1985;Errede 1992;Byun et aI. 1996), including poly (vinyl chloride) Ranney 1995, 1996) and rubber (Gee 1942;Salomon and van Amerongen 1947;Scott and Magat 1949;Bristow and Watson 1958), as well as photographic gelatin Oohnsen 1996).…”
Section: The Swelling Of Artists' Paints In Organic Solvents Part 1mentioning
confidence: 98%